Recalcitrant Pyoderma Gangrenosum: Clinical Burden and Unmet Needs - Becker SL; Velasco R; Ortega-Loayza AG (Dove Medical Press, 2023)
Sarah L Becker,1,* Rose Velasco,2,* Alex G Ortega-Loayza1 1Department of Dermatology, Oregon Health & Science University, Portland, OR, USA; 2University of Illinois College of Medicine, Chicago, IL, USA*These authors contributed equally to this workCorrespondence: Alex G Ortega-Loayza, Department of Dermatology, Oregon Health & Science University, 3303 S Bond Ave Building 1, 16th Floor, Portland, OR, 97239, USA, Tel +1 503-418-3376, Fax +1 503-494-6968, Email ortegalo@ohsu.eduAbstract: Pyoderma gangrenosum (PG) is a rare, autoinflammatory disease leading to aseptic ulcers which carries a significant disease burden and is often difficult to treat, with many patients failing first-line treatment and requiring additional therapies. Such cases are typically referred to in the literature as "recalcitrant", "refractory", or "resistant", though little is known about the clinical characteristics of such cases. We performed a narrative literature review to characterize patient demographics and clinical course associated with difficult to treat pyoderma gangrenosum cases in order to identify trends to guide future clinical management and therapeutic innovation. We identified 148 cases with clinical manifestations and associated patient demographics stratified by ulcer and patient features. Consistent with previous work, a greater prevalence of PG was observed among female patients and those with a history of inflammatory bowel disease, however interestingly despite an aggressive course to their PG, few patients had comorbidities complicating their disease course. Additionally, despite the requirement of three or more treatments for most patients' disease to resolve, the majority healed within the typical window observed in previous clinical studies with low rates of recurrence. Biologics were the most common medication patients were on at time of remission. Collectively, our results suggest a potential benefit for a reduced threshold for biologic initiation in PG patients and a need for standardization of language in the field to facilitate treatment outcomes comparisons and interventions.Keywords: pyoderma gangrenosum, recalcitrant, refractory, resistant, biologics